2014
DOI: 10.1124/mol.114.093799
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Vascular Smooth Muscle Kv7.4, Kv7.5, and Kv7.4/7.5 Channels by ML213 and ICA-069673

Abstract: Recent research suggests that smooth muscle cells express Kv7.4 and Kv7.5 voltage-activated potassium channels, which contribute to maintenance of their resting membrane voltage. New pharmacologic activators of Kv7 channels, ML213 (N-mesitybicyclo[2.2.1]heptane-2-carboxamide) and ICA-069673 N-(6-chloropyridin-3-yl)-3,4-difluorobenzamide), have been reported to discriminate among channels formed from different Kv7 subtypes. We compared the effects of ML213 and ICA-069673 on homomeric human Kv7.4, Kv7.5, and het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 51 publications
7
53
0
1
Order By: Relevance
“…4B); a slight suppression of the current observed in the presence of rolipram was not statistically significant. Subsequent application of the nonselective Kv7.2-Kv7.5 activator ML213 (10 mM) (Yu et al, 2011;Brueggemann et al, 2014a) robustly enhanced the MASMC Kv7 currents and this effect was reversed by the selective Kv7 channel blocker XE991 (10 mM) (Fig. 4B), demonstrating the expected pharmacological characteristics of the Kv7 currents and confirming our ability to detect an increase in current amplitude in these cells.…”
Section: Kt5720supporting
confidence: 72%
See 1 more Smart Citation
“…4B); a slight suppression of the current observed in the presence of rolipram was not statistically significant. Subsequent application of the nonselective Kv7.2-Kv7.5 activator ML213 (10 mM) (Yu et al, 2011;Brueggemann et al, 2014a) robustly enhanced the MASMC Kv7 currents and this effect was reversed by the selective Kv7 channel blocker XE991 (10 mM) (Fig. 4B), demonstrating the expected pharmacological characteristics of the Kv7 currents and confirming our ability to detect an increase in current amplitude in these cells.…”
Section: Kt5720supporting
confidence: 72%
“…4). A7r5 cells natively express only Kv7.5 channels (Brueggemann et al, 2007, whereas MASMCs predominantly express Kv7.4/Kv7.5 channels (Brueggemann et al, , 2014a. Insensitivity of MASMC Kv7.4/7.5 channels to rolipram was replicated when this same subunit combination was expressed in A7r5 cells, suggesting that the difference in regulation of native Kv7 currents between A7r5 cells and MASMCs relates primarily to the Kv7 channel subunit stoichiometry rather than to differences in PDE isoforms (Polson and Strada, 1996;Dunkerley et al, 2002;Maurice et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Although it is less potent than its related analog ICA-27243, ICA-069673 displays greater efficacy and improved selectivity for heteromeric K V 7.2/K V 7.3 over K V 7.1 channels (Amato et al, 2011). In contrast with retigabine, which binds to the pore region (S5 to S6) of K V 7.2-K V 7.5 channels (Gunthorpe et al, 2012), evidence suggests that ICA-069673 is among an emerging novel class of compounds known as "gating modifiers," named so for their ability to bind to the S1-S4 voltage-sensing domain of K V 7 channels Peretz et al, 2010;Brueggemann et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…ICA-069673 did not affect K V 7.1 channels, which are predominately expressed in the heart (Amato et al, 2011). A recent study on A7r5 smooth muscle cells demonstrated that ICA-069673 was effective in activating recombinantly expressed K V 7.4 channels (Brueggemann et al, 2014a). However, K V 7.4 channel protein expression was not observed in guinea pig DSM (Afeli et al, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…; Brueggemann et al . ). Several studies have suggested the possibility that certain KCNQ activators may act on a distinct site present in certain KCNQ subtypes.…”
Section: Introductionmentioning
confidence: 97%